ICRF193 potentiates the genotoxicity of etoposide - Masato Ooka; Leah Mitchell; Jinghua Zhao; Kouji Hirota; Ruili Huang; Takuya Abe; Menghang Xia (Scientific Reports)
Abstract ICRF193 is a catalytic inhibitor of Topoisomerase 2 (TOP2), one of the major targets in cancer therapy. Although ICRF193 has not been approved for clinical use, it has potential implications in chemotherapy. In this study, we aimed to investigate the use of ICRF193 in chemotherapy in co-treatment with other drugs. To identify compounds that have synergistic effects with ICRF193, we optimized a cytotoxicity assay with combinations of ICRF193 in a 1536-well plate format and screened 2678 compounds, including clinically approved and investigational drugs, for their cytotoxicity in the presence and absence of ICRF193. From the screening and confirmation assays, etoposide, a known TOP2-targeting drug, was found to have a synergistic effect with 200 nM ICRF193 across multiple cancer cell lines, including HCT116, MCF7, and T47D. On the other hand, ICRF193 suppressed the toxicity of etoposide at higher concentrations (> 10 µM). In the follow-up studies, we found that ICRF193 and etoposide synergistically induced DNA double-strand breaks and subsequent G2 phase accumulation. Interestingly, this synergistic effect was observed only with etoposide and not with other TOP2 inhibitors in the tested compound library. Taken together, our results indicate that ICRF193 has a specific functional interaction with etoposide that enhances its genotoxic potential.